THE IMPORTANCE OF EVALUATION MOTOR WITH THE PARTICIPANTS IN THE PROJECT PIRACEMA: RELIABILITY ANALYSIS OF MOTOR DEVELOPMENT SCALE (Fiep Bulletin - online, 2013)
The present study was a descriptive, exploratory, aims at presenting the motor profile of students participating in Project Spawning - "Swimming for People with Special Needs" - extension project at the University of Santa Cruz do Sul - UNISC - the acting 28 years, serving students from various pathologies. The project goal is to promote activities on the net so that students increase their repertoire of attitudes in the water and, when possible, also outside it. Participants were 35 students enrolled in APAE of Santa Cruz do Sul Project Spawning and participants, including 24 males and 11 females. Classes are held 3 times per week, 50 minutes per class, being attended three classes per day. To collect the data we used the kit Scale Development Motor (EDM), comprising the following: Fine Motor, Motricity Global, Balance, Body Scheme, Space Organization and Temporal Organization. Through the results, we found that the relationship between chronological age (IC) and General Motor Age (IMG) of the students is 21 ± 4.1 years. In Fine Motor results obtained 21 ± 4.6 years; in Global Kinetics, 21 ± 3.6 years; at equilibrium 21 ± 4.7 years; in Scheme Body 21 ± 3.45 years; spatial organization 21 ± 4.3 years, and the Temporal Organization, 21 ± 3.7 years. We conclude that the subjects of this study showed much lower standard engine in relation to their chronological age. These results may be related to the pathologies of the students because they were not taken into consideration. From the results of these evaluations, adjustments were made in the planning and organization of activities provided to these subjects in class aquatic project.
Keywords: Motor Development; Evaluation; impaired persons.